AN EPIDEMIOLOGICAL OVERVIEW OF DENGUE HEMORRHAGIC FEVER (DHF) CASES IN KEDIRI REGENCY DURING 2017-2021: Gambaran Epidemiologi Kasus Demam Berdarah Dengue (DBD) di Kabupaten Kediri Tahun 2017-2021 - Faradillah Amalia Febrianti; Eny Qurniyawati; Muhammad Atoillah Isfandiari; Nayla Mohamed Gomaa Nasr (Universitas Airlangga, 2023)
Background: Dengue Hemorrhagic Fever (DHF) is a communicable disease with rapid spread and the potential to cause death. In 2019, Kediri District had the fourth-highest number of DHF cases in East Java Province and was reported to have experienced a DHF outbreak. Objective: This study aimed to describe dengue cases in Kediri District in 2017-2021 under non-pandemic and COVID-19 pandemic conditions. Methods: Using a total sampling technique, descriptive research with a case series design was conducted using secondary data from the Health Profiles and the Central Bureau of Statistics of Kediri District in 2017-2021. The studied variables included the number of dengue cases, sex, age, area, population, population density, morbidity rate, Lateral Flow Immunoassay (LFI), and rainfall. Data were analyzed using an epidemiological approach based on people, places, and times and visualized with tables and diagrams. Results: The majority of DHF cases occurred in males and the 5-14 years age group in both the COVID-19 non-pandemic (52.88%; 55.96%) and COVID-19 pandemic conditions (51.14%; 58.56%). The incidence rate (IR) increased with population density and the number of dengue cases in the non-COVID-19 pandemic. It decreased with a decrease in dengue cases when the population density increased during the COVID-19 pandemic. Under all conditions, high dengue cases were found in months with high rainfall. Conclusion: The pattern of DHF incidence in Kediri District in 2017-2021 is mostly in males and the age group of 5-14 years, when there is an increase in population density, and in January.